2007
DOI: 10.1136/bjsm.2007.034827
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to rock climbing in young climbers

Abstract: Key questions regarding the training and physiological qualities required to produce an elite rock climber remain inadequately defined. Little research has been done on young climbers. The aim of this paper was to review literature on climbing alongside relevant literature characterising physiological adaptations in young athletes. Evidence-based recommendations were sought to inform the training of young climbers. Of 200 studies on climbing, 50 were selected as being appropriate to this review, and were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
4
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 94 publications
5
102
4
3
Order By: Relevance
“…30,32 Some evidence on the physiological demands of competitive elite youth climbing exists, 39,46,47 as well as on the anthropometric requirements. 24 Of late, more articles are addressing the impact of rock climbing on the overall health-related fitness of youth.…”
Section: Overview Of Rock Climbing Benefits In Youthmentioning
confidence: 99%
“…30,32 Some evidence on the physiological demands of competitive elite youth climbing exists, 39,46,47 as well as on the anthropometric requirements. 24 Of late, more articles are addressing the impact of rock climbing on the overall health-related fitness of youth.…”
Section: Overview Of Rock Climbing Benefits In Youthmentioning
confidence: 99%
“…Este tipo de trabajo no es adecuado para principiantes y, en particular, para los adolescentes cuyos huesos y ligamentos no están plenamente desarrollados (Dennis, Finch, & Farhart, 2005;Caine et al, 2006;Magra, Caine, & Maffulli, 2007;Morrison & Schöffl, 2007).…”
Section: -Propuesta Didáctica Para Evitar Las Posibles Lesionesunclassified
“…In summary, most of the studies found that overuse injuries are mainly affecting the upper extremity, while acute traumatic injuries are more frequently located on the lower extremity [1,76] . Also, besides the acute lower limb injuries the incidence of chronic feet problems increases in the higher levels of sport climbing [23,25,75,77,78] . Scientific research in rock climbing up to date focused extensively on upper limb injuries.…”
Section: Et Al Feet Injuries In Rock Climbersmentioning
confidence: 99%
“…This may be based on the fact that various upper limb injuries as e.g., pulley injuries [44,60,79] , lumbrical shift syndrome [32] , extensor hood syndrome [80] or epiphyseal fatigue fractures in young climbers [63] are new pathologies and rather specific for the sport. Studies and reports on lower limb injuries and overuse syndromes are rare [23,25,33,75,77,78] . Nevertheless as e.g., the study by Neuhof et al [2] showed, that the mostly injured region were the feet (19.2%), these injuries are of a high importance and need to be examined further [1] (Table 1) [61] .…”
Section: Et Al Feet Injuries In Rock Climbersmentioning
confidence: 99%